EXPLORING SPIRITUAL WELL-BEING AMONG SURVIVORS OF COLORECTAL AND LUNG CANCER - Clay, Kimberly S. (2010)
This descriptive, exploratory study is part of a larger observational study of the quality of cancer care delivered to population-based cohorts of newly-diagnosed patients with lung and colorectal cancer. The current study explores the role of spiritual well-being in adjustment to life after the cancer diagnosis, utilizing the Functional Assessment of Chronic Illness Therapy – Spiritual Well-being – Expanded (FACIT-Sp-Ex) Scale. Survey data collected from 304 newly-diagnosed cancer survivors were analyzed to explore important aspects of spirituality, such as sense of meaning in one’s life, harmony, peacefulness, and a sense of strength and comfort from one’s faith. Spiritual well-being scores, particularly meaning/peace, were statistically significant for African Americans, women and colorectal cancer survivors. These findings amplify a need for oncology social workers and other practitioners to assess spiritual well-being in cancer survivors in an effort to strengthen psychosocial treatment plans. Implications for social work practice and research are discussed.